ENHANCING BUSINESS PERFORMANCE OF CV PRIMANTO PANGAN SELARAS INDONESIAN FRUIT CHIPS GOES INTERNATIONAL - Raga Etsenna Wattimena; Andi Kristian; Wai Wai Soe; Bojia Ran; Selena Delgado; Ahmad Alfahad; Dhuha Alomar (International Journal of Applied Business and International Management, 2017)
Javanis Food is a trademark of Malang kripik factory which is a form of entrepreneurship spirit, based on the processing technology of various fruits and vegetables into chips as food. We want to develop the potential of chips into a delicious and nutritious product, and perform the production stages based on non-chemical research experience and hygienic supervision. Since 2015, Javanis Food has conducted production trials and cooperated with fruit farmer groups in Malang and extends to East Java. Javanis Food learns with farmers and suppliers to produce quality standards of raw materials, through desirable quality standard education and discussion during the development and planting of fruit trees. Javanis Food wants to continue to improve the partnership standards with fruit farmers, suppliers and business partners throughout Indonesia, to produce internationally-qualified local products.